Tinjauan Tentang Proses Peran Lembaga Bantuan Hukum dalam Penanganan Perkara Perdata di Pengadilan Negeri Karawang Berdasarkan UU No 16 Tahun 2011 Tentang Bantuan Hukum - Lubis, Adyan; Abas, Muhamad; Sitorus, Leonardo; Aripin, Rizal; Sihotang, Alex Antonius (Universitas Pahlawan Tuanku Tambusai, 2025)
The existence of Legal Aid Posts (POSBAKUM) is regulated by Supreme Court Regulation Number 1 of 2014 concerning Guidelines for Providing Legal Services for Disadvantaged People in Court. The legal counseling method is a communicative approach carried out through the systematic delivery of juridical information by sources to the audience. Another critical finding was the public's confusion when it was explained that there were three channels for providing legal aid in operation: POSBAKUM in court, OBH accredited by the Ministry of Law and Human Rights, and independent legal aid institutions. Community service activities regarding the role of legal aid institutions in handling civil cases in Karawang Regency reveal a critical gap between the normative guarantees of Law Number 16 of 2011 and the reality of accessibility of justice for underprivileged communities. Based on the findings and critical reflections from this service activity, a series of comprehensive and sustainable strategic actions are needed to optimize the role of legal aid institutions in ensuring access to justice for underprivileged communities in Karawang Regency.